Experience of foreign countries in ensuring procedural guarantees of the rights of participants in criminal proceedings - A. V. Piddubna (Bulletin of Kharkiv National University of Internal Affairs)
The fundamental rights, freedoms and legitimate interests of a person, being subject to the greatest restrictions during criminal proceedings, are guaranteed by the existence of substantive and procedural rules in the legislation aimed at protecting, defending and implementing procedural guarantees of participants in criminal proceedings. The dynamics of social, political, economic and legal life, the social mentality of today, as well as convergence processes determine the adaptation of national criminal procedure legislation to International law. However, the issues of adaptation of national legislation to the provisions of foreign legislation in terms of guaranteeing each participant in criminal proceedings the protection, defence and realisation of their rights, freedoms and legitimate interests in accordance with international standards remain controversial. At the same time, there are a number of gaps and inconsistencies in the provisions of the criminal procedure legislation, the gradual elimination of which will allow Ukraine to reach the international level as a state that guarantees each participant in criminal proceedings the protection, defence and exercise of their rights, freedoms and legitimate interests in accordance with European standards, as well as reduce the number of applications to the European Court of Human Rights.